A THAMESSIDE TOWN IN THE EARLY FIFTEENTH CENTURY: KINGSTON UPON THAMES AND ITS PEOPLE. Issue 1 (1st April 2022) - Robinson, David
Abstract : Kingston upon Thames Borough Archives include a small number of documents created in the course of the government of the town in the late fourteenth century and the first half of the fifteenth. There are three rentals of (?)1383, 1417 and c.1427; Court of Record rolls, 2 October 1406, December 1415–September 1416 and October 1440; annual view of frankpledge rolls, 1434–5, 1437 and 1439–41; an extract from pleas before the county justices, 1 October 1414; and a membrane of property pleas with writs, 1419. They were probably preserved initially in support of the townsmen's claims to exercise certain rights of jurisdiction. The purpose of the present article is to show that these materials, although scanty, are sufficient to provide a quite detailed picture of the town and its people. No attempt is made here to use the wider range of archives which would be needed for a comprehensive account nor is material from other towns used for comparative purposes. It is not claimed that the material studied here challenges the accepted narrative of late medieval urban history. It will be sufficient if attention is drawn to the potential for those studying the history of their own towns to use such local archives as survive to bring into focus the lives of their medieval townspeople in intimate detail.